2021
DOI: 10.1002/14651858.cd013155.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for bleeding oesophageal varices in people with decompensated liver cirrhosis: a network meta-analysis

Abstract: Treatment for bleeding oesophageal varices in people with decompensated liver cirrhosis: a network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 294 publications
0
5
0
1
Order By: Relevance
“…Although the superiority of EVL over EIS for the secondary prophylaxis of variceal hemorrhage has been proven based on moderate-certainty evidence ( 11 ), the better emergency endoscopic treatment for acute EVB remains controversial. Lo GH, et al compared the short-term efficacy and safety of emergency EIS with EVL in the arresting of acute EVB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the superiority of EVL over EIS for the secondary prophylaxis of variceal hemorrhage has been proven based on moderate-certainty evidence ( 11 ), the better emergency endoscopic treatment for acute EVB remains controversial. Lo GH, et al compared the short-term efficacy and safety of emergency EIS with EVL in the arresting of acute EVB.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic injection sclerotherapy (EIS) and endoscopic variceal ligation (EVL) are favored non-surgical treatment strategies of endoscopy for managing acute EVB ( 7 10 ). A newly published meta-analysis has demonstrated the superiority of EVL over EIS in terms of fewer adverse events ( 11 ). Several trials comparing long-term EIS to EVL gave separate data for EVB, however, failing to show any differences between the two ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic variceal ligation (EVL) and endoscopic injection sclerotherapy have demonstrated in randomized controlled trials that their single overall outcome is better than other treatments, with decreased rebleeding, mortality, and variceal eradication; recent network meta-analysis and some multicenter retrospective studies have demonstrated EVL's superiority as a single treatment for active bleeding; the addition of other medical treatments could potentiate the overall results, such as the dual therapy of EVL and NSBB [ 56 , 59 ]. Transjugular intrahepatic portosystemic shunt (TIPS) has been shown to control and reduce some of the pathophysiology behind the BEV with high efficacy.…”
Section: Reviewmentioning
confidence: 99%
“…Ainda à nível de tratamento, ficou claro que os procedimentos cirúrgicos são recomendados num plano terciário, sendo mais utilizadas em casos específicos em que haja indicação, priorizando os tratamentos conservadores prezando assim pela qualidade de vida de cada paciente, corroborando com (Roberts, 2021).…”
Section: Conclusãounclassified